Team game tournaments to improve the enjoyment and basic technical of handball student-athletes: A randomized-controlled trial - Usra, Meirizal; Setiawan, Edi; Octara, Kevin; Lesmana, Irfan Benizar; Ciocan, Vasile Catalin (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
There has been an increase in the use of the TGT learning model in physical education, but the lack of TGT research which is associated with enjoyment and basic technical in handball is a gap in research. The objective of this study was to evaluate the effect of using TGT in improving student-athlete enjoyment and basic techniques. This study applied the true experiment method. The participants were student-athletes from junior high school 46 Palembang (n=30). Physical education classes was conducted in experimental group through TGT, while the control group received conventional PE. The results showed that there were no differences in the value of enjoyment and basic techniques in the experimental and control groups before the experiment, but there were differences after the experiment. Based on the Paired sample t-test it was proven that after teaching handball for 4 weeks through TGT, student-athlete enjoyment and basic techniques increased significantly, but the experimental group had a much larger mean value. Thus, it can be concluded that TGT was an effective method for physical education teacher to create enjoyment and improve basic techniques in handball. Future research needs to be carried out such as testing the effects of TGT using mixed methods research.